2020
DOI: 10.21203/rs.3.rs-89427/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive Analysis of Gut Microbiota of a Healthy Population and Covariates Affecting Microbial Variation in Two Large Japanese Cohorts

Abstract: Background: Inter-individual variations in gut microbiota composition are observed even among healthy populations. As gut microbiota in Japanese populations exhibit a unique composition compared to others, it is informative to conduct large-scale Japanese cohort studies for a comprehensive understanding of the association between healthy gut microbiota and host status. The aim of the present study was to elucidate the integrated and non-redundant factors associated with gut microbiota composition within the Ja… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The diversity of gut microbiota is closely related to the environment, and the composition of gut microbiota in different regions is diverse. For example, one study reported that the gut microbiota of the Japanese population is exceedingly different from other populations (Park et al, 2021). Therefore, the current research may have specific limitations.…”
Section: Intracranial Aneurysmmentioning
confidence: 87%
“…The diversity of gut microbiota is closely related to the environment, and the composition of gut microbiota in different regions is diverse. For example, one study reported that the gut microbiota of the Japanese population is exceedingly different from other populations (Park et al, 2021). Therefore, the current research may have specific limitations.…”
Section: Intracranial Aneurysmmentioning
confidence: 87%
“…The factors that affect gut microbiota are complex and intersecting, such as age, ethnicity, geography, host genetics, gender, and lifestyle factors (Park et al, 2021). Previous studies have shown that region and ethnicity have an impact on human gut microbiota (Mueller et al, 2006;Gaulke and Sharpton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…31 Covariates used included common gut microbiota perturbing factors that were baseline age, sex, smoking, medications, prevalent diseases, and body mass index (BMI). 32,33 An individual was flagged as a smoker if they had smoked within 6 months of baseline investigation. Adjusted medications included dummy variables for use of blood pressure medication (reported on the questionnaire), psychotropics (ATC: N05 and N06), and metformin use (ATC: A10BA02).…”
Section: Follow-upmentioning
confidence: 99%